MADAE-PRO: UM PROCESSO BASEADO NO CONHECIMENTO PARA ENGENHARIA DE DOMÍNIO E DE APLICAÇÕES MULTIAGENTE. - COSTA, Adriana Leite (2009)
The interest in the agent-oriented paradigm development has increased in recent years. This is due mainly to the increasing complexity of current software that requires new characteristics as autonomy behavior. In the agent-oriented paradigm, the software has no longer a strictly predictable behavior, has from the control over their own behavior and can make decisions based on observations the environment and inferences upon its knowledge base. A set of meth and process have been already proposed for agent-oriented software engineering. Domain Engineering is a process for the development of a reusable application family in a particular domain problem, and Application Engineering, the one for the construction of a specific application in a family based on the reuse of software artifacts in the application family previously produced in the Domain Engineering process. MADAE-Pro is an ontology-driven process for multi-agent domain and application engineering which promotes the construction and reuse of agent-oriented applications families. The process is specified in a formal representation language, thus avoiding ambiguous interpretations. Another differential of MADAE-Pro is the reuse of software support in all levels of abstraction, from the requirements to the deployment.